DERMAPLAT® AS AN EDUCATIONAL TOOL: FEEDBACK FROM MEDICAL STUDENTS IN DERMATOLOGICAL PRACTICE - Soares, Tássia Gabrielle Ponte Carneiro; Soares, Ronan Pardo; da Silva, Lucas Melgaço; Alves, Sarah Roque; Martins, Luisa Eulália Brito Oliveira; de Bayma Rebouças, Maria Eduarda Cruvinel; dos Santos, Marina Livia Portela; Lopes, Thais Melo; Medeiros, Melissa Soares (Editora Impacto Científico, 2025)
This study evaluated the usability and acceptability of the DermaPlat® digital platform among medical students at two Brazilian institutions, investigating whether a digital resource focused on elementary lesions supports diagnostic reasoning in dermatology and integrates with academic and primary care routines. A quantitative, cross-sectional, and experimental study was conducted using the System Usability Scale (SUS) and the Technology Acceptance Model (TAM), as well as internal consistency and correlation analyses. The results indicated a favorable user experience and high acceptance, with an intuitive interface, fluid navigation, and objective content, useful for independent study and quick reference during supervised consultations. A direct relationship was observed between perceived usability and acceptance, suggesting that ergonomics and clear flow are determinants of adoption. The conclusion is that DermaPlat® is promising as a complement to dermatology education, fostering continuous learning and earlier, safer decisions throughout clinical training. DOI: 10.56238/edimpacto2025.060-010